Relationship between Menarche Age and the Incidence of Primary Dysmenorrhea in Christian Junior High School Students of Citra Bangsa Mandiri Kupang City - Giovani Maria Fallo; Kristian Ratu; Nimas Prita R. K. Wardani; Teguh Dwi Nugroho (Jurnal Biologi Tropis, 2026)
Primary dysmenorrhea ranks among the most prevalent menstrual issues in teenagers, impacting their everyday life and general well-being. The age at which menstruation begins has frequently been linked to the likelihood of experiencing dysmenorrhea; however, previous studies have produced mixed results. The goal of this research was to examine the connection between the age of menarche and the incidence of primary dysmenorrhea in female students at Kristen Citra Bangsa Mandiri Junior High School in Kupang. This investigation utilized an analytical observational method with a cross-sectional approach. A total of 54 students were chosen using purposive sampling according to specific inclusion and exclusion standards. Menarche age was classified as early (younger than 12 years), normal (12 to 14 years), and late (older than 14 years). The WaLIDD Score was employed to evaluate primary dysmenorrhea. The data were processed using the chi-square test, with a significance threshold set at p<0.05. The findings indicated that 55.6% of female students had a normal age for the start of menstruation, while 44.4% started early. The occurrence of primary dysmenorrhea was found to be 77.8%, with mild cases at 38.9%, moderate cases at 31.5%, and severe cases at 7.4%. Those who did not experience primary dysmenorrhea made up 22.2% of the respondents. The statistical analysis yielded a p=0.90 value. There was no significant link between the age of menarche and the prevalence of primary dysmenorrhea among students at Citra Bangsa Mandiri Christian Junior High School in Kupang City.